PEMANFAATAN MODEL TAKSONOMI STRUCTURE OF THE OBSERVED LEARNING OUTCOME (SOLO) DALAM PENGEMBANGAN PERANGKAT EVALUASI PADA KOMPETENSI MENULIS SISWA SMP - Fahrudin Eko Hardiyanto (LPPM Universitas Pekalongan, 2012)
This research discussed the development of evaluation device using the SOLO taxonomy, ranking in unistrucural level assessment form, multi-structural, relational, and abstract. Statements of the problems in this study were 1) how the characteristics of the taxonomic structure of the evaluation of Observed Learning Outcome (SOLO) in writing competence, 2) how the principles of evaluation device development, 3) how is evaluation device draft, and 4) how the effectiveness of the evaluation device. This study used a model of Research and Development (R & D), which is the research and development of the writing evaluation competency device of Junior Class VII with the subject of research were students and teachers in the Junior Class VII in Pekalongan. The results of this study were 1) Characteristics of the evaluation based on the SOLO taxonomy writing competence junior school VII grade students based on the results of questionnaires from 40 respondents and the corresponding perception of teachers based on the results of questionnaires of 4 respondents, 2) the development of the Principles evaluation based on SOLO taxonomy writing competence junior class VII include (a) the principle of the development of a appropriate type of question (b) the principle of development of multiple choice questions (c) the principle of the development of the essay question (d) principles for the development of question type for critical thinking skills (e) the principle of development types of question for solving the problem ability, 3) Evaluation device draft based on SOLO taxonomy literary reading competence of VII grade of junior school in the form of conceptual material, lesson plans samples, evaluation grid, the card question, package of question completed with instructions, the answer key and scoring and 4) The evaluation is based on SOLO taxonomy effective reading competence literary views of validity, reliabilities, index of level of difficulty, and the distinguishing features about. The question package which was examined was as many as 10 trials contained eight valid questions. Numbers/ scores on the evaluation of reliability is reached about 1.786 with categories tested reliable. In the aspect of difficulty index obtained data from 10 about 3 question items was the excellent category, two items about both categories, with category 3 question items was enough, and one qustion items was bad category. While on the aspects of the different power, from 10 question items has 3 excellent, 3 questions were enough, and one question item was bad category.Keywords: SOLO taxonomy, development, evaluation device